Sustainable Tourism Business Practices in Rote Island: Striking a Balance Between Economic Growth and Environmental Conservation - Sari Natonis; Eunike M. Gegung; Arjuna Purba; Junita C. Nenabu (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
This study aims to analyze the practices, challenges, and strategies for implementing sustainable tourism in Rote Island, East Nusa Tenggara. Using a mixed methods approach with a case study design, the research explores the balance between economic growth, environmental conservation, and socio-cultural sustainability. Quantitative data were collected through surveys involving tourists, business operators, local communities, and government representatives, while qualitative data were obtained from in-depth interviews and field observations. The PLS-SEM analysis revealed that business sustainability and profitability are the most dominant factors in strengthening the local economy (R² = 0.717), followed by environmental and socio-cultural aspects. The findings indicate that tourism practices in Nembrala remain at a moderate to low level across the three pillars of sustainability, characterized by limited waste management systems, low community participation, and unequal distribution of economic benefits. Local community involvement is largely confined to labor roles, while business ownership is dominated by outside investors. This situation creates economic disparities and weak integration of local cultural values into tourism products. The study emphasizes the importance of collaborative governance involving government, businesses, and local communities in strategic decision-making, as well as the adoption of the triple bottom line principles (profit, people, planet) in tourism business models. The implications highlight the need for long-term, regulation-based policies, MSME capacity strengthening, and community empowerment to build inclusive, resilient, and globally competitive tourism destinations.